Effect of Antioxidants on High-Temperature Stability of Renewable Bio-Oils Revealed by an Innovative Method for the Determination of Kinetic Parameters of Oxidative Reactions - Fabio Mollica; Marco Lucarini; Cinzia Passerini; Claudio Carati; Silvia Pavoni; Lucia Bonoldi; Riccardo Amorati (Antioxidants, 2020)
Bio-oils employed for various industrial purposes, such as biodiesel production, undergo extensive oxidation and degradation during transformation processes. Therefore, it is extremely important to predict their stability at high temperature. We report herein a new procedure based on the optically detected profile of headspace O2 concentration during isotherms at 130 °C for evaluating the oxidation kinetic parameters of several bio-oil feedstocks. The slope of O2 consumption and the induction period duration were related to the oil characteristics (molecular structure, acidity, and presence of intrinsic antioxidants or metals). The increase of the induction time caused by a standardized propyl gallate addition yielded a semiquantitative value of radical generation rate. Investigated oils included used cooking oils; mono-, di-, and triglycerides from natural sources; free fatty acids; transesterified oils; and their blends. With respect to other methods, this characterization presents the advantage of disentangling and evaluating the role of both fatty acids composition and naturally occurring antioxidants, and allows the development of rational strategies for antioxidant protection of oils and of their blends.